Identification of circRNA–miRNA–mRNA Regulatory Network and Crucial Signaling Pathway Axis Involved in Tetralogy of Fallot - Kan, Zunqi; Yan, Wenli; Wang, Ning; Fang, Yuqing; Gao, Huanyu; Song, Yongmei (Frontiers in Genetics, 2022)
Tetralogy of Fallot (TOF) is one of the most common cyanotic congenital heart diseases (CHD)worldwide; however, its pathogenesis remains unclear. Recent studies have shown that circular RNAs (circRNAs) act as “sponges”" for microRNAs (miRNAs) to compete for endogenous RNA (ceRNA) and play important roles in regulating gene transcription and biological processes. However, the mechanism of ceRNA in TOF remains unclear. To explore the crucial regulatory connections and pathways of TOF, we obtained the human TOF gene, miRNA, and circRNA expression profiling datasets from the Gene Expression Omnibus (GEO) database. After data pretreatment, differentially expressed mRNAs (DEmRNAs), microRNAs (DEmiRNAs), and circRNAs (DEcircRNAs) were identified between the TOF and healthy groups, and a global triple ceRNA regulatory network, including circRNAs, miRNAs, and mRNAs based on the integrated data, was constructed. A functional enrichment analysis was performed on the Metascape website to explore the biological functions of the selected genes. Then, we constructed a protein-protein interaction (PPI) network and identified seven hub genes using the cytoHubba and MCODE plug-ins in the Cytoscape software, including BCL2L11, PIK3R1, SOCS3, OSMR, STAT3, RUNX3, and IL6R. Additionally, a circRNA–miRNA–hub gene subnetwork was established, and its enrichment analysis results indicated that the extrinsic apoptotic signaling pathway, JAK-STAT signaling pathway and PI3K-Akt signaling pathway may be involved in the pathogenesis of TOF. We further identified the hsa_circ_000601/ hsa-miR-148a/BCL2L11 axis as a crucial signaling pathway axis from the subnetwork. This study provides a novel regulatory network for the pathogenesis of TOF, revealing the possible molecular mechanisms and crucial regulatory pathways that may provide new strategies for candidate diagnostic biomarkers or potential therapeutic targets for TOF.